Model of Gut Absorption from Carbohydrates with Maximum Rate of Exogenous Glucose Appearance in Type 1 Diabetes. Issue 5 (1st September 2016) - Yamamoto Noguchi, Claudia Cecilia; Hashimoto, Shogo; Furutani, Eiko; Sumi, Shoichiro
Abstract : An accurate mathematical representation of the impact of carbohydrates on postprandial glucose-insulin metabolism in type 1 diabetes (T1D) is essential for the development of model-based diabetes-related technologies. In this study, the physiological representation of a previous model of gut absorption from carbohydrates is enhanced by including a maximum rate of exogenous glucose appearance as observed in clinical studies in the literature. Simulation results for the same four representative carbohydrate-rich foods with varying glycemic index values as in our previous study, in addition to a sugary beverage, show that the postprandial glycemic excursion relates more closely to clinical data of postprandial glycemic excursion in patients with T1D.